Metal fluoride molten salt coated silicon-based negative electrode material and preparation method thereof

By coating the silicon-based negative electrode material with a low-melting-point composite metal fluoride molten salt, a uniform and continuous lithium fluoride protective layer is formed, which solves the volume expansion and low initial efficiency problems of the silicon-based negative electrode material and improves the cycle performance and initial efficiency of the lithium-ion battery.

CN120657087APending Publication Date: 2025-09-16ANHUI QINGZHI TECH DEV CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510798564.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-16
Publication Date
2025-09-16

AI Technical Summary

Technical Problem

Existing silicon-based negative electrode materials in lithium-ion batteries have problems with poor cycle performance and low initial efficiency due to volume expansion and the production of lithium silicate byproducts during the first charge and discharge. Existing lithium fluoride coating methods make it difficult to form a uniform and continuous protective layer.

Method used

A low-melting-point composite metal fluoride molten salt is mixed with a silicon-based negative electrode material and heated in a protective atmosphere to form a uniform and continuous lithium fluoride coating layer, which is spread on the silicon surface through the fluidity of the molten salt to construct a protective layer.

Benefits of technology

Effectively inhibit the volume expansion and pulverization of silicon-based negative electrode materials, improve structural stability, improve initial efficiency and cycle stability, and avoid high temperature damage to the silicon material structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005450511210000071
    Figure BDA0005450511210000071
Patent Text Reader

Abstract

The invention discloses a metal fluoride molten salt coated silicon-based negative electrode material and a preparation method thereof, and relates to the technical field of lithium ion battery negative electrode materials. The lithium fluoride-containing coating layer is constructed on the surface of the silicon negative electrode material by using the low-melting-point composite metal fluoride molten salt at a relatively low temperature through a molten salt coating method, so that the first effect and the cycling stability of the silicon-based negative electrode material can be effectively improved, and the preparation method has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion battery negative electrode materials, and in particular to a metal fluoride molten salt-coated silicon-based negative electrode material and a preparation method thereof. Background Art

[0002] At present, carbon-based materials represented by artificial graphite are the main materials for lithium-ion battery negative electrodes. At this stage, commercial graphite negative electrode materials are close to their theoretical specific capacity limit (372mAh / g). In order to further improve the energy density of batteries, finding negative electrode materials with higher specific capacity has become the focus of industry research. Silicon-based negative electrode materials have a theoretical specific capacity of 4200mAh / g and are the lithium-ion battery negative electrode materials with the highest known specific capacity. However, due to their huge volume effect (>300%), during use, the volume expansion of silicon will cause the SEI film to expand, and then break, and eventually cause the electrode to fail. Therefore, the cycle performance of silicon-based negative electrode materials is poor. In addition, silicon-based negative electrode materials will consume lithium to produce by-products such as lithium silicate during the first charge and discharge process, resulting in low first efficiency. In order to further improve the performance of lithium-ion batteries, it is necessary to improve the first efficiency and cycle performance of silicon-based negative electrode materials.

[0003] Lithium fluoride is an important component of the SEI film. Pre-constructing an artificial SEI layer containing lithium fluoride on the surface of the negative electrode is beneficial to improving the interfacial stability of the silicon negative electrode, thereby improving the first effect and cycle performance of the silicon negative electrode material. At present, the method of constructing a lithium fluoride layer on the surface of the negative electrode is mainly to add fluoroethylene carbonate to the electrolyte. During the battery cycle, FEC is the first to decompose, and lithium fluoride and organic polymers are generated in situ on the electrode surface. However, this method is difficult to form a uniform and continuous lithium fluoride layer on the electrode surface, and the protective effect on the silicon negative electrode is quite limited. Some studies have also proposed methods of forming a lithium fluoride coating layer on the surface of silicon negative electrode materials by solution blending, physical grinding and other means, but these methods have problems such as easy introduction of impurities and discontinuous coating layers, which have limited improvement in the electrochemical performance of silicon-based negative electrode materials. Summary of the Invention

[0004] Based on the technical problems existing in the background technology, in order to further improve the initial efficiency and cycle performance of silicon-based negative electrode materials, the present invention proposes a metal fluoride molten salt coated silicon-based negative electrode material and a preparation method thereof.

[0005] The present invention proposes a method for preparing a metal fluoride molten salt-coated silicon-based negative electrode material, which comprises uniformly mixing the silicon negative electrode material and the composite metal fluoride molten salt, and then heating the mixture in a protective atmosphere to obtain the negative electrode material;

[0006] The melting point of the composite metal fluoride molten salt is 400-800°C. The preparation method comprises the steps of uniformly mixing lithium fluoride and one or more other metal fluorides, heating the mixture in a protective atmosphere to melt the mixture, keeping the mixture warm for a period of time, and then cooling the mixture.

[0007] The temperature of the heating treatment is ≤800° C., and the temperature of the heating treatment is not lower than the melting point of the composite metal fluoride molten salt.

[0008] Preferably, the heating treatment time is 1 to 3 hours.

[0009] In the method for preparing the metal fluoride molten salt-coated silicon-based negative electrode material, conventional post-treatment steps, such as cooling and grinding, may be further included after the heating step.

[0010] In the method for preparing the metal fluoride molten salt coated silicon-based negative electrode material, the method for uniformly mixing the silicon negative electrode material and the composite metal fluoride molten salt can adopt conventional mixing methods in the art, such as stirring and ball milling.

[0011] In the present invention, the other metal fluorides refer to metal fluorides other than lithium fluoride, and can be selected from, for example, sodium fluoride, potassium fluoride, magnesium fluoride, calcium fluoride, zirconium fluoride, cerium fluoride or lanthanum fluoride.

[0012] Preferably, the composite metal fluoride molten salt is made of lithium fluoride and calcium fluoride in a mass ratio of 0.79:0.21;

[0013] Alternatively, the composite metal fluoride molten salt is made of lithium fluoride, sodium fluoride, and potassium fluoride in a mass ratio of 0.465:0.115:0.42;

[0014] Alternatively, the composite metal fluoride molten salt is made of lithium fluoride, sodium fluoride, and zirconium fluoride in a mass ratio of 0.55:0.22:0.23;

[0015] Alternatively, the composite metal fluoride molten salt is made of lithium fluoride, sodium fluoride and zirconium fluoride in a mass ratio of 0.42:0.29:0.29.

[0016] Preferably, in the method for preparing the composite metal fluoride molten salt, the holding time is 0.5 to 2 hours.

[0017] In the method for preparing the composite metal fluoride molten salt, a conventional post-processing step, such as grinding, may be further included after the cooling step.

[0018] In the method for preparing the composite metal fluoride molten salt, the method for uniformly mixing lithium fluoride and one or more other metal fluorides can adopt conventional mixing methods in the art, such as stirring and ball milling.

[0019] Preferably, the mass ratio of the silicon negative electrode material to the composite metal fluoride molten salt is 100:0.1-10.

[0020] Preferably, the silicon negative electrode material is selected from nano-silicon, nano-hollow silicon, porous silicon, silicon monoxide, silicon-carbon material or silicon monoxide / carbon material.

[0021] In the present invention, the protective atmosphere refers to one of nitrogen and inert gases (such as argon and helium) or a mixed atmosphere of several of them.

[0022] The present invention also proposes a metal fluoride molten salt-coated silicon-based negative electrode material, which is prepared by the preparation method.

[0023] The beneficial effects of the present invention are as follows:

[0024] The present invention mixes a low-melting-point composite metal fluoride molten salt formed by melting lithium fluoride and other metal fluoride salts with a silicon negative electrode material, and heats the mixture at a relatively low temperature to form a coating containing lithium fluoride on the surface of the silicon negative electrode material, thereby obtaining a metal fluoride molten salt coated silicon-based negative electrode material. The present invention uses a molten salt coating method to construct a coating containing lithium fluoride on the surface of the silicon negative electrode material using a low-melting-point composite metal fluoride molten salt at a relatively low temperature. When coated, the composite metal fluoride molten salt is in a fluid state, which can flow and spread on the surface of the silicon negative electrode material, so that the formed coating has good uniformity and continuity, thereby further enhancing the protective effect on the silicon negative electrode material, better suppressing the volume expansion and pulverization of the silicon-based negative electrode material during the charge and discharge process, and improving the structural stability. At the same time, due to the low temperature of the heating coating, the damage to the structure of the silicon material and the negative effect on the electrochemical performance of the high temperature are avoided. In summary, the present invention can effectively improve the first effect and cycle stability of the silicon-based negative electrode material and has good application prospects. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is described in detail below through specific embodiments.

[0026] In the following examples and comparative examples, the particle size of nano-silicon is 20 to 50 nm.

[0027] Example 1

[0028] Preparation of composite metal fluoride molten salt:

[0029] Weigh 7.9 g of lithium fluoride and 2.1 g of calcium fluoride and place them in an agate ball mill, ball mill them at a speed of 300 r / min for 1 hour, then place them in a glassy carbon crucible, heat them to 800°C under an argon atmosphere to melt them, keep them warm for 1 hour, grind them after cooling, and pass them through a 200 mesh sieve to obtain 0.79LiF-0.21CaF2 composite metal fluoride molten salt with a melting point of 762°C.

[0030] Preparation of metal fluoride molten salt coated silicon-based anode materials:

[0031] Weigh 0.5 g of the composite metal fluoride molten salt obtained above and 10 g of nano-silicon and place them in an agate ball mill, ball mill them at a speed of 300 r / min for 1 hour, then place them in a glassy carbon crucible, heat to 800°C under an argon atmosphere, keep warm for 2 hours, and grind them to 200 mesh after cooling.

[0032] Example 2

[0033] Preparation of composite metal fluoride molten salt:

[0034] 4.65 g of lithium fluoride, 1.15 g of sodium fluoride and 4.2 g of potassium fluoride were weighed and placed in an agate ball mill, ball-milled at a speed of 300 r / min for 1 h, then placed in a glassy carbon crucible, heated to 1000°C under an argon atmosphere to melt it, kept warm for 1 h, ground after cooling, and passed through a 200 mesh sieve to obtain 0.465LiF-0.115NaF-0.42KF composite metal fluoride molten salt with a melting point of 454°C.

[0035] Preparation of metal fluoride molten salt coated silicon-based anode materials:

[0036] Weigh 0.5 g of the composite metal fluoride molten salt obtained above and 10 g of nano-silicon and place them in an agate ball mill, ball mill them at a speed of 300 r / min for 1 hour, then place them in a glassy carbon crucible, heat to 500°C under an argon atmosphere, keep warm for 2 hours, grind after cooling, and pass through a 200-mesh sieve to obtain the product.

[0037] Example 3

[0038] Preparation of composite metal fluoride molten salt:

[0039] Weigh 5.5 g of lithium fluoride, 2.2 g of sodium fluoride and 2.3 g of zirconium fluoride into an agate ball mill, ball mill them at a speed of 300 r / min for 1 h, then place them in a glassy carbon crucible, heat them to 1000 ° C under an argon atmosphere to melt them, keep them warm for 1 h, grind them after cooling, and pass them through a 200 mesh sieve to obtain 0.55LiF-0.22NaF-0.23ZrF4 composite metal fluoride molten salt with a melting point of 572 ° C.

[0040] Preparation of metal fluoride molten salt coated silicon-based anode materials:

[0041] Weigh 0.5 g of the composite metal fluoride molten salt obtained above and 10 g of nano-silicon and place them in an agate ball mill, ball mill them at a speed of 300 r / min for 1 hour, then place them in a glassy carbon crucible, heat to 600°C under an argon atmosphere, keep warm for 2 hours, grind after cooling, and pass through a 200-mesh sieve to obtain the product.

[0042] Example 4

[0043] Preparation of composite metal fluoride molten salt:

[0044] Weigh 4.2 g of lithium fluoride, 2.9 g of sodium fluoride and 2.9 g of zirconium fluoride into an agate ball mill, ball mill them at a speed of 300 r / min for 1 h, then place them in a glassy carbon crucible, heat them to 1000°C under an argon atmosphere to melt them, keep them warm for 1 h, grind them after cooling, and pass them through a 200 mesh sieve to obtain 0.42LiF-0.29NaF-0.29ZrF4 composite metal fluoride molten salt with a melting point of 460°C.

[0045] Preparation of metal fluoride molten salt coated silicon-based anode materials:

[0046] Weigh 0.5 g of the composite metal fluoride molten salt obtained above and 10 g of nano-silicon and place them in an agate ball mill, ball mill them at a speed of 300 r / min for 1 hour, then place them in a glassy carbon crucible, heat to 500°C under an argon atmosphere, keep warm for 2 hours, grind after cooling, and pass through a 200-mesh sieve to obtain the product.

[0047] Comparative Example 1

[0048] Comparative Example 1 is nano-silicon without any treatment.

[0049] Comparative Example 2

[0050] Preparation of lithium fluoride-coated silicon-based negative electrode materials:

[0051] Grind the lithium fluoride and pass it through a 200-mesh sieve. Then weigh 0.5 g of the ground lithium fluoride and 10 g of nano-silicon and place them in an agate ball mill. Ball mill them at a speed of 300 r / min for 1 hour. Then place them in a glassy carbon crucible and heat them to 900°C in an argon atmosphere to melt them. Keep warm for 2 hours, cool them down, grind them, and pass them through a 200-mesh sieve.

[0052] Comparative Example 3

[0053] Prepare the metal fluoride mixture:

[0054] Weigh 7.9 g of lithium fluoride and 2.1 g of calcium fluoride and place them in an agate ball mill, ball mill them at a speed of 300 r / min for 1 h, then grind them and pass them through a 200-mesh sieve to obtain the product.

[0055] Preparation of metal fluoride-coated silicon-based anode materials:

[0056] Weigh 0.5 g of the metal fluoride mixture obtained above and 10 g of nano-silicon, place them in an agate ball mill, ball mill them at a speed of 300 r / min for 1 h, then grind them and pass them through a 200-mesh sieve to obtain.

[0057] Comparative Example 4

[0058] Prepare the metal fluoride mixture:

[0059] Weigh 7.9 g of lithium fluoride and 2.1 g of calcium fluoride and place them in an agate ball mill, ball mill them at a speed of 300 r / min for 1 h, then grind them and pass them through a 200-mesh sieve to obtain the product.

[0060] Preparation of metal fluoride-coated silicon-based anode materials:

[0061] Weigh 0.5 g of the metal fluoride mixture obtained above and 10 g of nano-silicon and place them in an agate ball mill, ball mill them at a speed of 300 r / min for 1 hour, then place them in a glassy carbon crucible, heat to 800°C under argon atmosphere, keep warm for 2 hours, and grind them to 200 mesh after cooling.

[0062] Test example

[0063] Lithium-ion batteries were assembled using the metal fluoride molten salt-coated silicon-based negative electrode materials prepared in Examples 1 to 4, the nano-silicon of Comparative Example 1, and the silicon-based negative electrode materials of Comparative Examples 2 to 4 as negative electrode active materials. The electrochemical performance of each group of batteries was tested at 25°C.

[0064] Among them, the preparation method of the negative electrode plate and the lithium-ion battery includes the following steps: 95.7% of the negative electrode active material, 0.3% of the conductive agent single-walled carbon nanotubes and 4% of the binder PAALi (lithium polyacrylate) are mixed evenly in a mass ratio, and an appropriate amount of high-purity water is added to obtain a negative electrode slurry; the negative electrode slurry is coated on a copper foil, dried at 110°C in a vacuum drying oven for 10 hours, and rolled and punched to obtain a negative electrode plate; a lithium sheet is used as a counter electrode, and the electrolyte is composed of a lithium salt LiPF6, an additive FEC (fluoroethylene carbonate) and a solvent, wherein the concentration of the lithium salt LiPF6 is 1 mol / L, the content of the additive FEC is 5wt%, and the solvent is composed of EC (ethylene carbonate) and DEC (diethyl carbonate) in a volume ratio of 1:1; a button battery is assembled in a glove box under an argon atmosphere and charged and discharged at a rate of 0.1C.

[0065] The performance test results of each battery are shown in Table 1:

[0066] Table 1

[0067]

[0068] According to the test results in Table 1, it can be seen that:

[0069] The metal fluoride molten salt coated silicon-based negative electrode material of the present invention can significantly improve the first effect of silicon-based negative electrode material and improve its cycle stability. Comparative Example 1 uses untreated nano-silicon as the negative electrode material, and its first effect and capacity retention rate are both low. Comparative Example 2 uses lithium fluoride to melt-coat nano-silicon to obtain a silicon-based negative electrode material, and its first effect and specific capacity are also relatively low. This is because the melting temperature of a single lithium fluoride is too high, which affects the structure of the silicon material, and the coating layer structure formed by lithium monofluoride is not good. Comparative Example 3 uses a mechanical ball milling mixing method to prepare a metal fluoride-coated silicon-based negative electrode material, and its first effect and specific capacity are also relatively low. This is because the coating layer formed by the metal fluoride on the surface of the silicon is discontinuous, the coating is uneven, and the protection effect is not good. Comparative Example 4 does not prepare a molten salt first, but adopts a method of heating the product of the mechanical mixing of metal fluorides after mixing with nano-silicon. Its first effect and specific capacity are also relatively low. This is because there may be a phenomenon that some metal fluorides are not melted, resulting in the failure of metal fluorides to be evenly coated on the surface of the silicon.

[0070] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.

Claims

1. A method for preparing a metal fluoride molten salt-coated silicon-based negative electrode material, characterized in that: The silicon negative electrode material and the composite metal fluoride molten salt are mixed uniformly, and then heated in a protective atmosphere to obtain; The melting point of the composite metal fluoride molten salt is 400-800°C. The preparation method comprises the steps of uniformly mixing lithium fluoride and one or more other metal fluorides, heating the mixture in a protective atmosphere to melt the mixture, keeping the mixture warm for a period of time, and then cooling the mixture. The temperature of the heating treatment is ≤800° C., and the temperature of the heating treatment is not lower than the melting point of the composite metal fluoride molten salt.

2. The method for preparing a metal fluoride molten salt-coated silicon-based negative electrode material according to claim 1, characterized in that: The heating treatment time is 1 to 3 hours.

3. The method for preparing a metal fluoride molten salt-coated silicon-based negative electrode material according to claim 1, characterized in that: The other metal fluoride is selected from sodium fluoride, potassium fluoride, magnesium fluoride, calcium fluoride, zirconium fluoride, cerium fluoride or lanthanum fluoride.

4. The method for preparing a metal fluoride molten salt-coated silicon-based negative electrode material according to claim 1, characterized in that: The composite metal fluoride molten salt is made of lithium fluoride and calcium fluoride in a mass ratio of 0.79:0.21; Alternatively, the composite metal fluoride molten salt is made of lithium fluoride, sodium fluoride, and potassium fluoride in a mass ratio of 0.465:0.115:0.42; Alternatively, the composite metal fluoride molten salt is made of lithium fluoride, sodium fluoride, and zirconium fluoride in a mass ratio of 0.55:0.22:0.23; Alternatively, the composite metal fluoride molten salt is made of lithium fluoride, sodium fluoride and zirconium fluoride in a mass ratio of 0.42:0.29:0.

29.

5. The method for preparing a metal fluoride molten salt-coated silicon-based negative electrode material according to claim 1, characterized in that: In the preparation method of the composite metal fluoride molten salt, the holding time is 0.5 to 2 hours.

6. The method for preparing a metal fluoride molten salt-coated silicon-based negative electrode material according to claim 1, characterized in that: The mass ratio of the silicon negative electrode material to the composite metal fluoride molten salt is 100:0.1-10.

7. The method for preparing a metal fluoride molten salt-coated silicon-based negative electrode material according to claim 1, characterized in that: The silicon negative electrode material is selected from nano-silicon, nano-hollow silicon, porous silicon, silicon monoxide, silicon-carbon material or silicon monoxide / carbon material.

8. A metal fluoride molten salt coated silicon-based negative electrode material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Cited By

  • Silicon-carbon negative electrode material coated with metal fluoride and preparation method of silicon-carbon negative electrode material

    CN121641923A